2018
DOI: 10.1039/c8ra03833c
|View full text |Cite|
|
Sign up to set email alerts
|

A study on a telo21 G-quadruplex DNA specific binding ligand: enhancing the molecular recognition ability via the amino group interactions

Abstract: A symmetric ligand is synthesized composed of a core N-methylpyridinium scaffold and two parasubstituted benzyl groups through a flexible ethylene bridge to form a novel three-ring-conjugated system. The ligand system was found to have only weak background fluorescent signal in aqueous or physiological conditions and exhibited strong fluorescent signal enhancement targeting at telo21 Gquadruplex structure rather than other types of nucleic acids. The comparison study with two terminal groups (-N(CH 3 ) 2 versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In an attempt to probe the crucial factors in rational design of G4-selective ligands, our group has developed several ligand systems. We found that, apart from adopting a planar core molecular fragment to construct G4-ligands, the overall molecular size, 116 symmetry, 117,118 flexibility, 83 and the character of terminal groups [119][120][121][122] may affect the in vitro selectivity of the ligand toward G4-structures against RNA, single-and double-stranded DNA. Our study suggests that some smallsized molecular scaffolds including benzothiazole-benzofuroquinolinium, 123,124 benzothiazole-indolium, 125 1-methylquinolinium, 126 thiazole orange 81,84,127 and benzo[e]indole 128 are good molecular fragments for the design of fluorescent G4-ligands to achieve high discrimination ability, sensitivity and quantum yield targeting certain types of G4s for in vitro sensing and live cell imaging.…”
Section: G4-selective Fluorescent Ligands For Molecular Recognition A...mentioning
confidence: 99%
“…In an attempt to probe the crucial factors in rational design of G4-selective ligands, our group has developed several ligand systems. We found that, apart from adopting a planar core molecular fragment to construct G4-ligands, the overall molecular size, 116 symmetry, 117,118 flexibility, 83 and the character of terminal groups [119][120][121][122] may affect the in vitro selectivity of the ligand toward G4-structures against RNA, single-and double-stranded DNA. Our study suggests that some smallsized molecular scaffolds including benzothiazole-benzofuroquinolinium, 123,124 benzothiazole-indolium, 125 1-methylquinolinium, 126 thiazole orange 81,84,127 and benzo[e]indole 128 are good molecular fragments for the design of fluorescent G4-ligands to achieve high discrimination ability, sensitivity and quantum yield targeting certain types of G4s for in vitro sensing and live cell imaging.…”
Section: G4-selective Fluorescent Ligands For Molecular Recognition A...mentioning
confidence: 99%
“…[30,31] Some factors such as the symmetry, the electronic effects and the characteristics of the terminal functional groups of the ligands have been known to influence 4 strongly the binding affinity and discrimination signal in many examples. [32][33][34] In recent years, a number of thiazole-and styryl-based fluorescent ligands that showed good fluorescence sensing performance towards G-quadruplex nucleic acids have been reported. [35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…For the study of ligand-DNA interaction in vitro or in vivo, in order to achieve merit fluorescent signal discrimination and display higher affinity to interact with G4-DNA over duplex-DNA, the design of molecular scaffolds that are able to match with the G4-DNA binding pocket (G-quartet) is crucial. Some recent reports revealed that the feature of a binding ligand such as molecular shape [42], symmetry [43,44], the planarity and polarity of ligands [12,45,46] and the electronic effect of terminal groups [47][48][49], may have significant influence in the ligand-G4-DNA interaction specificity and affinity. In the present study, three new G4-DNA binding ligands based on a relatively rigid thiazole orange (TO) scaffold were synthesized by varying the molecular size and flexibility of the terminal substituent groups for probing the interaction characteristics of the G-quartet of telomeric G4-DNA because the understanding of binding site matching in rational drug design is essential.…”
Section: Introductionmentioning
confidence: 99%